Cholecysto-appendicostomy as partial internal biliary drainage in Progressive Familial Intrahepatic Cholestasis Type 1: A case report and review of literature - Yee Ian Yik; Mohd Yusran Othman; Ruey Terng Ng; Way Seah Lee (Elsevier, 2016)
Intractable pruritus secondary to bile salts retention in Progressive Familial Intrahepatic Cholestasis (PFIC) can be relieved surgically by diverting bile drainage from ileum to reduce bile salts reabsorption into entero-hepatic circulation. We are reporting on the successful biliary diversion in a child with PFIC, with the use of the appendix as a conduit to drain bile from gallbladder to the colon (cholecysto-appendicostomy).